The first new species of European Ascocotyle Looss, 1899 (Digenea: Heterophyidae) described in more than half a century - Gustinelli, Andrea; Caffara, Monica; Scaravelli, Dino; Fioravanti, Maria Letizia; Scholz, Tomáš (International journal for parasitology. Parasites and wildlife, 2022)
Ascocotyle (Phagicola) trentinii n. sp. is described based on adults from experimentally infected ducklings (Anas platyrhynchos domesticus) fed with metacercariae from the visceral serosa of the Mediterranean banded killifish, Aphanius fasciatus (Cyprinodontiformes: Aphaniidae), from coastal lagoons in northeastern Italy (Emilia-Romagna Region). The new species is placed into the subgenus Phagicola because of the presence of a single row of circumoral spines, vitelline follicles being confined between the ventral sucker and testes, and uterine loops not reaching anterior to the ventral sucker. Ascocotyle (P.) trentinii n. sp. differs from other members of the subgenus Phagicola, as well as other species of Ascocotyle, by the number (27-33) of circumoral spines which are 13.5-17 μm long and 3.5-5 μm wide, and by the morphology of a gonotyl which is composed of about 8 large refractile pockets. The occurrence of metacercariae in A. fasciatus indicates that the life cycle of the new species is completed in brackish water lagoons. It is the fourth species of Ascocotyle described in Europe and may be endemic to the Mediterranean region because its second (fish) intermediate host is endemic to this region.
Keywords: Trematoda; Italy; Brackish water; Ascocotyle trentinii n. sp.; Taxonomy; 28S rDNA; Aphanius fasciatus